Gender, Traumatic Events, and Mental Health Disorders in a Rural Asian Setting. (December 2013) - Axinn, William G.; Ghimire, Dirgha J.; Williams, Nathalie E.; Scott, Kate M.
Research shows a strong association between traumatic life experience and mental health and important gender differences in that relationship in the western European Diaspora; but much less is known about these relationships in other settings. We investigate these relationships in a poor rural Asian setting that recently experienced a decade-long armed conflict. We use data from 400 adult interviews in rural Nepal. The measures come from World Mental Health survey instruments clinically validated for this study population to measure depression, posttraumatic stress disorder, and intermittent explosive disorder. Our results demonstrate that traumatic life experience significantly increases the likelihood of mental health disorders in this setting, and that these traumatic experiences have a larger effect on the mental health of women than men. These findings offer important clues regarding the potential mechanisms producing gender differences in mental health in many settings.